Penegakan Hukum Keimigrasian Terhadap Tindak Pidana Human Trafficking Di Bengkalis Dalam Tinjauan Yuridis Normatif - Suzana, Ega; Lestari, Maria Maya; Rahmadan, Davit (Universitas Sang Bumi Ruwa Jurai, 2025)
The regulation of positive Indonesian law on human trafficking, as outlined in the Immigration Law, faces normative obstacles, especially in regions like Bengkalis. These obstacles include weak sanctions under immigration law and the absence of a legal framework to enforce commitments under international protocols, such as the Protocol Against Migrant Smuggling by Land, Sea, and Air, which Indonesia has signed. This lack of strong legislation has made Indonesia a preferred transit country for human smugglers, tarnishing its reputation and directly harming its interests. Additionally, overlapping duties between police investigators and Civil Servant Investigators (PPNS) often lead to disharmony and inefficiency in law enforcement. To address these challenges, amendments to Law Number 6 of 2011 concerning Immigration are urgently needed, alongside synchronization between national and international laws. Clear and effective implementing regulations should be drafted to resolve ambiguities, and the capacity of immigration law enforcers must be enhanced. Furthermore, jurisdictional boundaries in transnational cases need to be clarified to ensure effective and harmonious law enforcement against human trafficking crimes in regions like Bengkalis